FUNGSI HARTA DALAM PERSPEKTIF AL-QUR’AN - Wardah Rahman (Journal of Islamic Economic and Business Studies, 2023)
The research aims to examine the concepts and content contained in the Al-Qur'an regarding the function of wealth from the perspective of the Al-Qur'an. The discussion in this research consists of the meaning of assets, the function of assets from the perspective of the Al-Qur'an and the function of assets from the perspective of the Al-Qur'an. This research takes the form of a literature review, namely by examining the Al-Qur'an, books, journals and articles that are appropriate to this research. There are three problem formulations in this research, first, what is the meaning of property? Second, what is the status and position of wealth in the perspective of the Qur'an? Third, what is the function of wealth in the perspective of the Qur'an? The method used in this research is library research or literature review by collecting data and then analyzing data sources that are relevant to this research. The data sources were obtained from books, journals and other library materials. The results of this research are related to the function of wealth in the perspective of the Qur'an, namely: necessities of life (QS. Annisa verse 5), as jewelry for life (QS.Al-Kahf verse 46), glue of life (QS. An-nisa verse 95) , wealth functions to maintain humans (Al-baqarah verse 177), functions to strengthen ties of brotherhood (QS. Al-Ma'arij verse 24-25), functions as a test for its owner (QS. Al-munafiqun verse 9 and Ali Imran verse 14), serves to teach the importance of giving alms and providing the rights of the poor (QS Al-Baqarah verse 267-273).